2017
DOI: 10.3390/molecules22060955
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Mushroom Polysaccharides: A Review on Monosaccharide Composition, Biosynthesis and Regulation

Abstract: Mushrooms are widely distributed around the world and are heavily consumed because of their nutritional value and medicinal properties. Polysaccharides (PSs) are an important component of mushrooms, a major factor in their bioactive properties, and have been intensively studied during the past two decades. Monosaccharide composition/combinations are important determinants of PS bioactivities. This review summarizes: (i) monosaccharide composition/combinations in various mushroom PSs, and their relationships wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(83 citation statements)
references
References 85 publications
2
71
0
3
Order By: Relevance
“…A mixture of G. lucidum polysaccharides (known as GLP) is the main bioactive component in water-soluble extracts of the mushroom, and there is some evidence that GLP possesses potential anticancer activity (Sohretoglu & Huang, 2018). These metabolites influence the patient's innate and adaptive immune system, resulting in therapeutic immune modification (Berovič & Podgornik, 2015;Wang et al, 2017;Sudheer et al, 2018). Other metabolites found in extracts of Ganoderma have been found to be stimulators of neural stem cell proliferation in vitro and could be valuable treatments for neurodegenerative diseases (Yan et al, 2015).…”
Section: Relevance To Commercially Cultivated Fungimentioning
confidence: 99%
“…A mixture of G. lucidum polysaccharides (known as GLP) is the main bioactive component in water-soluble extracts of the mushroom, and there is some evidence that GLP possesses potential anticancer activity (Sohretoglu & Huang, 2018). These metabolites influence the patient's innate and adaptive immune system, resulting in therapeutic immune modification (Berovič & Podgornik, 2015;Wang et al, 2017;Sudheer et al, 2018). Other metabolites found in extracts of Ganoderma have been found to be stimulators of neural stem cell proliferation in vitro and could be valuable treatments for neurodegenerative diseases (Yan et al, 2015).…”
Section: Relevance To Commercially Cultivated Fungimentioning
confidence: 99%
“…Polysaccharides (PSs) are important and bioactive components of F. filiformis and other edible and medicinal mushrooms [47]. Glucans, such as lentinan, ganoderan, grifolan, and schizophyllan are well-studied PSs that can be produced by different fungi [48]. Previous studies have shown that F. velutipes polysaccharides (FVPs) have good immunomodulatory and anti-proliferation activities and improve learning and memory impairment in rats [4,5].…”
Section: Genes Involved In Polysaccharide Biosynthesis In F Filiformismentioning
confidence: 99%
“…Using intracellular nucleotide sugars as substrate, the EPS are synthesized in the cell membrane through the action of a large number of enzymes. Detailed information on the role of some of these enzymes such as the α-phosphoglucomutase is summarized in the review of Wang et al [12], who especially focused on EPS biosynthesis pathways, and on prospects for controlling biosynthesis of EPS with enhanced bioactivity. Supposed biological functions of the extracellular polymeric substances comprise supporting matrix adhesion, immobilizing extracellular enzymes, counteracting dehydration of the hyphae, storing excess nutrients, and contributing to lignin degradation [13,14].…”
Section: Submerged Cultivation Of Basidiomycotamentioning
confidence: 99%